New stegosaurian (Ornithischia, Thyreophora) remains from Jurassic-Cretaceous transition beds of Valencia province (Southwestern Iberian Range, Spain) - Ruiz-omeñaca, J.I.; Company, J.; Pereda Suberbiola, X. (Journal of Iberian Geology, 2010)
New stegosaurian remains have been recently recovered from the Jurassic-Cretaceous transition sandstones of the Villar del Arzobispo Formation (Tithonian-Berriasian) in the Valencia province, eastern Spain. Specimens consist of two partially articulated (or closely associated) postcranial skeletons. The Baldovar specimen is composed of appendicular bones (scapula, femur) and two pairs of dermal tail spines, two of them articulated with two distal caudal vertebrae. The second specimen, unearthed in the vicinity of La Yesa village, consists of dorsal vertebrae and ribs, fragments of caudal centra and an incomplete femur. The new specimens are tentatively referred to the clade Dacentrurinae and may belong to Dacentrurus on the basis of features observed on the dorsal vertebrae and caudal dermal spines. Stegosaurs are represented so far in the Jurassic-Cretaceous transition of Spain by Dacentrurus. The presence of other taxa (Stegosaurus, Miragaia) in Spain, recently documented in the Late Jurassic of Portugal, cannot be attested on the basis of the currently recorded material.